THE INFLUENCE OF MOTIVATION AND WORK-LIFE BALANCE ON THE PRODUCTIVITY OF FINAL STUDENTS OF THE BACHELOR OF MANAGEMENT PROGRAM IN THE EMPLOYEE CLASS - Indah Friska Pradiana; Abdul Bahits; Ahmad Mukhlis (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
This study aims to analyze the effect of motivation and work-life balance on the productivity of final year students of the Bachelor of Management Program in the employee class at Bina Bangsa University, Serang, Banten. The study used a quantitative approach with an associative causality design. The study population was 537 final year students of the Bachelor of Management Program in the employee class in the 2025/2026 academic year. Based on the Slovin formula with a 10% error rate, a sample of 85 respondents was obtained. Data were collected through a questionnaire using a Likert scale and analyzed using multiple linear regression, t-test, F-test, and coefficient of determination. The results showed that motivation had a positive and significant effect on student productivity, with a regression coefficient of 0.192, t-test of 2.216, and a significance of 0.029. Work-life balance also had a positive and significant effect on productivity, with a regression coefficient of 0.462, t-test of 6.127, and a significance of 0.000. Simultaneously, motivation and work-life balance had a significant effect on student productivity with an F-test of 87.368 and a significance of 0.000. The R-square value of 0.681 indicates that 68.1% of the variation in productivity can be explained by these two variables. Work-life balance is the most dominant variable with a Beta value of 0.632. This finding emphasizes the importance of role balance and strengthening motivation in increasing the productivity of employee-level students.